Harry Potter's Occlusion: Report of a Case of Pumpkin Seed Bezoar Rectal Impact - Gentile, Maurizio; Vergara, Lorenzo; Schiavone, Vincenzo; Cestaro, Giovanni; Sivero, Luigi (Frontiers in Surgery, 2022)
Bezoar is a term from Arabic‎ bāzahr, “bezoar” or ultimately from Middle Persian pʾtzhl pādzahr, “antidote, bezoar”ægagropile o egagropile.(2-3-4) It was believed to have the power of a universal antidote that works against any poison, and a glass containing a bezoar could neutralize any poison poured into it. In science, it is a mass of hair or undigested vegetable matter, found in a human or animal's intestines, similar to a hairball. Otherwise, the name could derive from a kind of Turkish goat whose name is just bezoar. Usually, it is found trapped in every part of the gastrointestinal system and must be distinguished by pseudobezoar which is an indigestive object voluntarily introduced into the digestive tract. The most common causes are: a previous gastric surgery such as a gastric band (for weight loss) or gastric bypass, a reduced stomach acid (hypochlorhydria) or decreased stomach size, a delayed gastric emptying, typically due to diabetes, autoimmune disorders, or mixed connective tissue disease. Seed bezoars are usually found in the rectum of patients without predisposing factors, causing constipation and pain. Rectal impaction is common after ingestion of seeds while a true occlusion is rare. Although several cases of phytobezoars composed of various types of seeds are reported in literature, bezoars of pumpkin seeds have rarely been reported. The authors report a case of fecal impaction by pumpkin seeds bezoar with abdominal pain: a difficulty to void with subsequent rectal inflammation and hemorrhoid enlargement was observed. The patient underwent a successful manual disimpaction.